Digital Transformation and Taxpayer Compliance: A Study of Key Factors Based on Maqasid Syariah Principles - Valifauzy, Annindi Galih; Witono, Banu; Zulfikar, Zulfikar (International Journal of Artificial Intelligence Research, 2024)
This study aims to investigate the factors influencing taxpayer compliance, particularly focusing on the role of digital transformation, with a framework rooted in the principles of Maqasid Syariah. A quantitative approach was employed, utilizing surveys and analyzing data with structural equation modeling (SEM) to evaluate the relationships among variables. The study reveals that tax knowledge, social norms, service quality, and sanctions significantly influence taxpayer compliance. Digital transformation plays a crucial moderating role, enhancing the impact of tax knowledge on compliance, thus reducing barriers to understanding tax regulations.Practical Implications: To improve tax compliance, governments should focus on enhancing tax education and fostering positive social norms surrounding taxpaying. Strengthening service quality, especially through digital platforms, will make tax processes more accessible, efficient, and transparent, ultimately increasing voluntary compliance. This study contributes to the existing literature by introducing the concept of Maqasid Syariah to the study of taxpayer compliance and digital transformation, offering new insights into the intersection of Islamic values and modern tax practices This study aims to investigate the factors influencing taxpayer compliance, particularly focusing on the role of digital transformation, with a framework rooted in the principles of Maqasid Syariah. A quantitative approach was employed, utilizing surveys and analyzing data with structural equation modeling (SEM) to evaluate the relationships among variables. The study reveals that tax knowledge, social norms, service quality, and sanctions significantly influence taxpayer compliance. Digital transformation plays a crucial moderating role, enhancing the impact of tax knowledge on compliance, thus reducing barriers to understanding tax regulations.Practical Implications: To improve tax compliance, governments should focus on enhancing tax education and fostering positive social norms surrounding taxpaying. Strengthening service quality, especially through digital platforms, will make tax processes more accessible, efficient, and transparent, ultimately increasing voluntary compliance. This study contributes to the existing literature by introducing the concept of Maqasid Syariah to the study of taxpayer compliance and digital transformation, offering new insights into the intersection of Islamic values and modern tax practices.